The Game as a Didactic Resource for Mathematics at the University: Experience in several Engineering Degrees - García Manzanas, Rodrigo; Frías Domínguez, María Dolores (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This work presents the results from a teaching innovation project focused on the inclusion of simple games, combined with Information and Communication Technologies and group dynamics, as a support tool in the learning of seven subjects in the field of Mathematics, taught in the first courses of different Degrees of Engineering. The participating teaching team has verified that the proposed methodology increases the motivation and active participation of the students, who have highlighted the usefulness of the implemented games in their learning process.